Silicon is dependent on hydrogen sulphide to improve boron toxicity tolerance in pepper plants by regulating the AsA-GSH cycle and glyoxalase system. (October 2020) - Kaya, Cengiz; Ashraf, Muhammad; Al-Huqail, Asma A.; Alqahtani, Moneerah A.; Ahmad, Parvaiz
Abstract: The role of endogenous hydrogen sulphide (H2 S) in silicon-induced improvement in boron toxicity (BT) tolerance in pepper plants was studied. Two-week old seedlings were subjected to control (0.05 mM B) or 2.0 mM BT in a nutrient solution. These two treatments were combined with 2.0 mM Si. BT caused considerable reduction in biomass, chlorophyll a & b, photosystem II maximum quantum efficiency ( F v/ F m), glutathione and ascorbate in the pepper seedlings. However, it enhanced malondialdehyde (MDA) and hydrogen peroxide, electrolyte leakage, proline, H2 S, and activities of catalase, superoxide dismutase, peroxidase, and L-DES. Silicon stimulated growth, proline content and activities of various antioxidant biomolecules and enzymes, leaf Ca 2+, K + and N, endogenous H2 S and L-DES activity, but reduced H2 O2 and MDA contents, membrane leakage and leaf B. Silicon-induced B tolerance was further enhanced by 0.2 mM NaHS, a H2 S donor. A scavenger of H2 S, hypotaurine (0.1 mM HT), was supplied together with Si and Si + NaHS to assess the involvement of H2 S in Si-induced BT tolerance of pepper plants. Hypotaurine inverted the positive role of Si on the antioxidant defence system by reducing endogenous H2 S, but NaHS supply along with Si + HT reversed the negative effects of HT, showing that H2 S participated in Si-induced BT tolerance of pepper plants. Highlights: Boron toxicity (BT) decreased plant growth and increased oxidative stress. Silicon (Si) reversed the oxidative stress and BT-induced growth inhibition. Si activated l -cysteine desulfhydrase (L-DES) and enhanced hydrogen sulphide (H2 S). Si enhanced antioxidants, K + and Ca 2+ contents and reduced B in the pepper plants. H2 S scavenger, hypotaurine (HT) reversed the H2 S synthesis and antioxidant defence systems, and aggravated oxidative stress.